The role of change agents in sustainable public procurement projects - Grandia, Jolien (Public money & management, 2015)
In the procurement process the decisions of project teams determine if the potential of sustainable procurement is attained. To optimize this, project teams should be encouraged to adopt new behaviour. The academic literature awards an encouraging role to the change agent. A comparison of the role of change agents in seven Dutch public procurement projects shows that change agents play an important role in sustainable procurement projects and help project teams progress towards sustainable procurement.